(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Laparoscopic cholecystectomy is currently thought as a surgical procedure that can be done with less risk of complications. However, intraoperative and postoperative complications were existing in 56 (15.01%) patients. Open surgery is the case when laparoscopic cholecystectomy fails to be proceeded with due to many causes such as difficult Calot triangle dissection and empyema of gallbladder. The high occurrence of cholecystitis in the group of patients aged 40-60 (56%) with 151 female and 59 males initiating the floor to many arguments that may help give a good understanding for such a problem. Iatrogenic perforation of gallbladder was the most common cause of intraoperative complications. Wound infection was the most cause of postoperative complications. Difficult Calot triangle dissection was the most common cause to convert to open surgery.